2017
DOI: 10.1590/s0100-204x2017001100017
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of productive and reproductive traits in multiple-breed dairy cattle populations

Abstract: -The objective of this work was to determine whether the random regression model using linear splines (RRMLS) is suitable to estimate the genetic parameters for productive and reproductive traits of a multiple-breed dairy cattle population, as well as to investigate the effect of the genetic group of the progeny on the genetic merit of the sire. The multiple-trait model (MTM) and the RRMLS with one knot fitted for every genetic group were used to obtain the genetic parameters. Records of 1/2 Holstein + 1/2 Gyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…In the current study, the heritability estimate for 305MY was 0.11 ± 0.005, and the repeatability estimate was 0.33 ± 0.003. In previous studies with Girolando cattle, heritability and repeatability estimates were higher than the estimates found in this study, with reported heritability values ranging from 0.15 to 0.35 (Ribeiro et al, 2017;Canaza-Cayo et al, 2018) and repeatability values ranging from 0.37 to 0.47 (Facó et al, 2008(Facó et al, , 2009.…”
Section: Genetic Parameterscontrasting
confidence: 76%
“…In the current study, the heritability estimate for 305MY was 0.11 ± 0.005, and the repeatability estimate was 0.33 ± 0.003. In previous studies with Girolando cattle, heritability and repeatability estimates were higher than the estimates found in this study, with reported heritability values ranging from 0.15 to 0.35 (Ribeiro et al, 2017;Canaza-Cayo et al, 2018) and repeatability values ranging from 0.37 to 0.47 (Facó et al, 2008(Facó et al, , 2009.…”
Section: Genetic Parameterscontrasting
confidence: 76%
“…The correlation among the random regression coefficients used to adjust the sires BV did not differ from zero (Table 7), as found by Vallée et al (2013) and Ribeiro et al (2017). Those authors demonstrated that the sire BV is related to the breed composition of their progeny and the BV obtained by purebred progeny records differs from that of crossbred progeny.…”
Section: Field Datamentioning
confidence: 66%
“…Multiple-breed variance and heritability is specific to each breed group (Figure 2 VanRaden et al, 2011); therefore, RRMLS are suitable to estimate the genetic parameters of productive and reproductive traits in multiple-breed populations, once it provides distinct estimates of sire BV for each progeny breed group (Ribeiro et al, 2017). The heritability for AFC, LL, and MY-305 has shown moderate magnitude ( Figure 2); thus, the selection process could modify the phenotypic means of these traits over the generations.…”
Section: Field Datamentioning
confidence: 99%
See 2 more Smart Citations